Recommendation System for Major University Determination Based on Student’s Profile and Interest - Desi Purwanti Kusumaningrum; Noor Ageng Setiyanto; Erwin Yudi Hidayat; Khafiizh Hastuti (Universitas Dian Nuswantoro and IndoCEISS, 2017)
Failure study on university students is one of the serious problems we face today. Data from the Centre for Education Statistics Research and Development of the Ministry of National Education Republic of Indonesia showed that the percentage of students graduate on time from 2001 to 2011 only reached 51.97%. In addition, cases of students dropping out at the beginning of the semester is also quite significant. One of the causes of failure of this study was the selection of major’s errors when applying to university. This study offers a selection subject recommendation system that builds on the profile data and student’s interest using the technique of Association Rule. Results of the rules of the relationship will then be matched with prospective students using questionnaires dynamic, so expect new students get recommendations more valid subject fit the profile and interest respectively. The system built on this research utilizes student data stored on the academic system of Dian Nuswantoro University. This model however can be adapted by all the universities that has a system of academic information. At the end of this system is expected to be used to minimize failures caused students study majors election mistakes